An estimate of the remainder term in the integral limit theorem in the case of convergence to the stable law - Mitalauskas, A. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. А. Миталаускас. Оценка остаточного члена в интегральной предельной теореме в случае сходимости к устойчивому законуA. Mitalauskas. Liekamojo nario įvertinimas integralinėje ribinėje teoremoje konvergavimo į stabilų dėsnį atveju